Renovation as Tool for Production Development - S. A. Voinova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers production process as multi-level system of interconnected elements. Problems pertaining to production renovation including renovation of its elements have been analyzed in the paper.